Market Day Sebagai Sarana Pembentukan Karakter Kewirausahaan Pada Anak - Muhammad Ghozali; Rahayu Apridayanti (Kreativasi : Journal of Community Empowerment, 2022)
School is a place that plays an effective role in shaping the character of children in which many breakthroughs are activated, one of which is the market day program. This activity is a means of teaching and growing the entrepreneurial character of students whose contents contain a lot of commendable attitudes. This research was conducted at SDIT Insan Kamil, Melawi Regency using a qualitative approach. The techniques used are observation, interviews and documentation to the research subjects consisting of principals, teachers, and parents of students. The results of the study indicate that the market day program in this educational institution has been formed through the school's vision of forming a rabbinic generation, intelligent, and competitive globally. Implementation is carried out in collaboration with parents starting from mentoring, supervision, product management, and marketing which are taught routinely to students so that the impact of the market day program is found that it can foster entrepreneurial character including being cheerful (attending and participating in learning), getting used to a healthy lifestyle, cooperate with parents, good communication, thorough, never give up, tenacious and always grateful (setting aside profits for the afterlife).